Strengthening Air Quality Management in Accra, Ghana : Improved Pollution Management and Reduced Environmental Health Risk in Accra-Tema Metropolitan Area - Final Report - Odoi, Justice; Kleiman, Gary (World Bank, Washington, DC, 2022)
Ambient concentrations of fine particulate matter (PM) are high and remain a key driver of the deleterious health effects of air pollution. Current air quality conditions present an unacceptable health burden for the population of Greater Accra Metropolitan Area (GAMA) and are not in line with international guidelines for air quality. To address the global challenge of pollution mitigation, the pollution management and environmental health (PMEH) multi-donor partnership was established in 2014 to make links between air pollution, human health, climate change, and growth priorities, through overarching analytical work and country specific support. This report is intended to summarize the achievements of Ghana’s PMEH program. This report has been drafted primarily for the benefit of communicating the impact of the PMEH project more effectively. The report begins with an introductory chapter that provides context on air pollution in Ghana and the GAMA, specifically. It draws mostly on academic research and recent World Bank analysis conducted for the Ghana country environmental analysis that was supported in part, through PMEH activities. A short chapter follows that provides some context on the PMEH program and the Accra pilot. Then the core outputs and resulting outcomes of the PMEH activities are presented with supporting details to show how each aspect contributed to the next iteration of the GAMA air quality management plan mid-term review that is currently underway. Finally, several sets of recommendations are presented that draw from the World Bank as well as several other development partners that have been working on air quality in Ghana to provide a comprehensive view of how this important work can be taken forward as Environmental Protection Agency (EPA) Ghana continues to address the challenges that air quality presents for a sustainable future in Accra and across Ghana.